2021
DOI: 10.1177/20503121211043710
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic utilization, sensitivity, and cost in the medical intensive care unit of a tertiary care teaching hospital in Nepal

Abstract: Background: High utilization and irrational use of antibiotics in an intensive care unit increases microbial resistance, morbidity, mortality, and costs. Objective: This study aimed to evaluate the utilization, sensitivity and cost analysis of antibiotics used in the medical intensive care unit of a tertiary care teaching hospital of Nepal. Methods: A prospective cohort study was conducted on patients admitted to the medical intensive care unit at a tertiary care teaching hospital in central Nepal from July to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…However, the total expenditure reported in our study was much lesser than reported in similar studies, which might be due to the fact that these studies included only intensive care unit patients. 28,29 In our study, aminopenicillins and beta-lactamase inhibitors were the highest prescribed AMMs, followed by nitroimidazoles, aminoglycosides and fluoroquinolones, which was similar to what was reported in other studies. 15,30 Though the consumption of carbapenems, polymixins, glycopenptides, lincomycins and teicoplaninlike higher AMMs was the highest in high-income regions, our study reported significantly lower expenditure on these AMMs.…”
Section: Discussionsupporting
confidence: 90%
“…However, the total expenditure reported in our study was much lesser than reported in similar studies, which might be due to the fact that these studies included only intensive care unit patients. 28,29 In our study, aminopenicillins and beta-lactamase inhibitors were the highest prescribed AMMs, followed by nitroimidazoles, aminoglycosides and fluoroquinolones, which was similar to what was reported in other studies. 15,30 Though the consumption of carbapenems, polymixins, glycopenptides, lincomycins and teicoplaninlike higher AMMs was the highest in high-income regions, our study reported significantly lower expenditure on these AMMs.…”
Section: Discussionsupporting
confidence: 90%
“…While in the Emergency Department of a tertiary care hospital in Saudi Arabia, the average cost of prescribed antibiotics was equivalent to 17.8 ± 11.6 USD only [ 43 ]. Another study in the medical intensive care unit (ICU) of a tertiary care teaching hospital in Nepal showed that the average cost of antibiotics per patient was 47.67 ± 63.73 USD [ 44 ]. A study in India reported that the average cost of antibiotics per patient in the ICU was 32.58 USD [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitatively, in terms of DDD/100 bed-days, azithromycin (46.66), doxycycline (22.53), teicoplanin (22.52), and ceftriaxone (16) were the most frequently used antimicrobials in our study. Comparatively, the DDD/100 bed-days for the six most commonly prescribed antibiotics were much lesser for doxycycline (8.7), piperacillin/tazobactam (7.8), ceftriaxone (6.2), azithromycin (6.1), metronidazole (5.1), and meropenem (4.8) in a study by Marasine et al [ 26 ]. In another study conducted in western Nepal, penicillin, fluoroquinolones, second-generation cephalosporins, and third-generation cephalosporins were used at rates of 55.1, 5.34, 0.82, and 13.74 DDD/100 bed-days respectively [ 27 ].…”
Section: Discussionmentioning
confidence: 99%